Analyzing Hospital’s Management Information System Based on Patient’s and Employee’s Perception Using EUCS Method - Aqil Farras; Hustinawati Hustinawati (Indonesian Journal of Multidisciplinary Science, 2022)
SIMRS is a system built to manage patient data in order to develop resources and improve hospital quality. As one of the newly implemented health support systems, the implementation of SIMRS needs to be observed. One of the indicators in the successful implementation of the system is the satisfaction of the end users of the system. User satisfaction (user satisfaction) is one indicator of the success of the development of information systems. Therefore, the research aims at analyzing the exact topic. EUCS is one of the research instruments that can be used to measure the success of information systems. In this study 5 EUCS instruments were used, namely content, accuracy, format, ease of use of users, timeliness of information systems and 3 additional variables, namely training, user satisfaction (user satisfaction)) and system benefits (net benefit). The results of this study indicate that accuracy (accuracy), format, user convenience (easy to use) timeliness of information systems (timeliness) and training (training) are proven to increase user satisfaction while content (content) has not been proven to have an effect. User satisfaction of integrated information systems has been proven to increase net benefits / organizational performance.